Prevention of renal ischemia/reperfusion injury in rats using acetylcysteine after anesthesia with isoflurane - Mansano,André Marques (2012)
PURPOSE: To evaluate the effect of N-acetylcysteine, as a renoprotective agent, when administered early after anesthesia induction, against ischemia/reperfusion injury in rats anesthetized with isoflurane. METHODS: Eighteen male Wistar rats weighing > 300g were anesthetized with isoflurane. The internal jugular vein and the left carotid artery were dissected and cannulated. The animals were randomly divided into GAcetyl, receiving intravenous N-acetylcysteine, 300mg/kg, and GIsot, isotonic saline. After 30 minutes, right nephrectomy was performed and the left renal artery was clamped during 45 minutes. The animals were sacrificed after 48 hours and blood samples were taken after anesthetic induction and upon sacrificing of the animals to evaluate blood creatinine. The kidneys were sent for histological analysis. RESULTS: The variation in serum creatinine was 2.33mg/dL ± 2.21 in GAcetyl and 4.38mg/dL ± 2.13 in GIsot (p=0.074). Two animals presented intense tubular necrosis in GAcetyl, compared to 5 in GIsot. Only GAcetyl presented animals free of tubular necrosis (two) and tubular degeneration (one). CONCLUSION: After renal ischemia/reperfusion, the rats which were given N-acetylcysteine presented less variation in serum creatinine and milder kidney injuries than the control group.